Using mobile telephones technology to address functionality of rural water supply systems in Uganda - Satya A. Chemisto (2013)
Uganda’s Ministry of Water and Environment last updated the information on coverage and functionality of the point water sources which lead to the establishment and publication of the 2010 Water Atlas. While the Ministry sees potential benefits from improved information about the state of rural water sources, it also realises that the real benefit for the water user is only achieved when information of a broken water point leads to prompt repair of the source. The challenge with the monitoring system is to improve not only information collection, but its flow that leads to action to improve water services on the basis of information collected. Real time information on functionality of water services is vital if functionality is to be increased and the use of modern technology is critical if this endeavour is to be achieved.